2018
DOI: 10.1051/swsc/2018015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of coronal mass ejections on parameters of high-speed solar wind: a case study

Abstract: -We investigate the case of disagreement between predicted and observed in-situ parameters of the recurrent high-speed solar wind streams (HSSs) existing for Carrington rotation (CR) 2118 (December 2011) in comparison with CRs 2117 and 2119. The HSSs originated at the Sun from a recurrent polar coronal hole (CH) expanding to mid-latitudes, and its area in the central part of the solar disk increased with the rotation number. This part of the CH was responsible for the equatorial flank of the HSS directed to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…This issue is not severe during solar minimum years, but becomes important during solar maximum years. One must also keep in mind that some of the rejected events may be real SIR/HSS events that are interacting with a simultaneously occurring ICME event near the ecliptic plane [see, e.g., Al-Shakarchi and Morgan, 2018;Shugay et al, 2018].…”
Section: Sir/hss Event Detection Algorithmmentioning
confidence: 99%
“…This issue is not severe during solar minimum years, but becomes important during solar maximum years. One must also keep in mind that some of the rejected events may be real SIR/HSS events that are interacting with a simultaneously occurring ICME event near the ecliptic plane [see, e.g., Al-Shakarchi and Morgan, 2018;Shugay et al, 2018].…”
Section: Sir/hss Event Detection Algorithmmentioning
confidence: 99%
“…A statistical study of Temmer et al (2017) in the time period 2011-2015 has shown that CMEs often are followed by a trailing region behind their rear that has declining speed and a duration up to several days, which is much longer than the average CME duration itself (about 1.3 days). As a result, powerful CMEs can cause disturbances of the interplanetary medium, which may lead to significant deviations in the CME arrival times and speeds from those initially predicted, especially in the case of slow CMEs (Möstl et al 2014;Corona-Romero et al 2017;Shugay et al 2018;Ravishankar & Michałek 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A statistical study of Temmer et al (2017) in the time period 2011 -2015 has shown that CMEs often are followed by a trailing region behind its rear with declining speed with duration up to several days which much longer than the average CME duration itself (about 1.3 days). As a result, powerful CMEs can cause disturbances of the interplanetary medium, which may led to significant deviations of the CME arrival times and speeds from the initially predicted, especially, in the case of slow CMEs (Möstl et al 2014;Corona-Romero et al 2017;Shugay et al 2018;Ravishankar & Micha lek 2019).…”
Section: Introductionmentioning
confidence: 99%